Плаха: [роман : 16+] / Чингиз Айтматов - Айтматов Чингиз Торекулович (Эксклюзив : Русская классика, 2019)
Экземпляры: ф. 3 (20190927) / Инвентарный номер: 110782 / Цена: 140.00 / Авт.знак: А 37 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6